JARAK ESTETIK DAN SEMANGAT ZAMAN PEMBACA NOVEL DIKTA DAN HUKUM KARYA DHI’AN FARAH (RESEPSI SASTRA JAUSS) - Karmiati, Karmiati; Nensilianti, Nensilianti; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze readers' understanding of the conflicts/plot found in the novel "Dikta dan Hukum," as well as readers' responses to the visualizations used in the novel to assess the aesthetic distance and zeitgeist of the readers. This research employs qualitative phenomenological research. The results of the analysis indicate that readers' responses are influenced by various factors, including aesthetic distance and the zeitgeist they experience. Diverse responses to the conflicts and plot in the novel reflect readers' varied perspectives on the quality of literary works. The use of character visualizations, such as Doyoung as Dikta, also becomes a point of evaluation for readers, with differing opinions on the suitability of these characters with the desired image of Dikta. This research reveals that readers provide complex and varied responses to literary works, influenced by their personal experiences, preferences, and cultural contexts. Thus, this study provides valuable insights into the interaction between readers and literary works, as well as the factors that influence their judgments of a work.